Roma Voices in History A Sourcebook - Marushiakova, Elena; Popov, Vesselin (Brill, 2021)
This ground-breaking book is an impressively extensive collection of primary historical sources in various languages that reflect the history of the Roma (formerly referred to as 'Gypsies' in local languages). The selection of the included materials reflects the authentic voice of the Roma them - selves, and presents their visions and the specific goals pursued by the Roma civic emancipation movement. The source materials are published in original and translated in English, and are accompanied by explanatory notes and summarising comments discussing the specific historical realities and their interrelation to the Romani emancipatory movement in Central and Eastern Europe, thus presenting a comprehensive picture of the historical processes.